STUDI AWAL BIG FIVE PERSONALITY TRAITS DALAM MENINGKATKAN PERILAKU INOVATIF STAFF YANG MEMBANTU PEKERJAAN AKUNTANSI DI TEMPAT KERJA PADA CV. “A” DI SURABAYA - Bella Lolita Santika D.; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
This research aims to provide an overview for real associated of how the implementaion of the big five personality traits to improving the innovative behavior of accounting staff in the workplace . From the research, it can be proven that personality traits of accounting staff have an influence on innovative behavior, so that through this research can be known how to improve the innovative behavior of accounting staff in accordance with their personality traits, to improve the quality of existing services in business entities and to achieve organizational business goals.This type of research is applied research with a qualitative approach. This researchattempts to provide recommendations on how to improve the innovative behavior of accounting staff according to their personality traits.